A visible light active, carbon–nitrogen–sulfur co-doped TiO2/g-C3N4 Z-scheme heterojunction as an effective photocatalyst to remove dye pollutants. Issue 27 (6th May 2021) - Huang, Zhen; Jia, Shuai; Wei, Jie; Shao, Ziqiang
Abstract : The CNS-TiO2 /g-C3 N4 photocatalyst with excellent visible light catalytic activity was successfully manufactured, benefiting from the construction of the Z-scheme heterojunction and the co-doping of heteroatoms (C, N and S). Abstract : Heterojunction formation and heteroatom doping could be viewed as promising strategies for constructing composite photocatalysts with high visible light catalytic activity. In this work, we fabricated a carbon, nitrogen and sulfur co-doped TiO2 /g-C3 N4 (CNS-TiO2 /g-C3 N4 ) Z-scheme heterojunction photocatalyst composite via one-step hydrothermal and calcination methods. Compared with pure TiO2 and g-C3 N4, the CNS-TiO2 /g-C3 N4 Z-scheme heterojunction photocatalyst possessed excellent degradation performance under visible light irradiation. Due to the formation of the Z-scheme heterostructure, the utilization rate of the photogenerated electrons–holes generated by the catalyst was increased, which enhanced the catalytic activity. Moreover, the heteroatom doping (C, N and S) could efficiently tailor the band gap of TiO2 and facilitate electron transition, contributing to enhancing the degradation ability under visible light. The CNS-TiO2 /g-C3 N4 -2 exhibited a superior photocatalytic degradation efficiency ( k = 0.069 min −1 ) for methyl orange dye (MO), which is higher than those of pure TiO2 ( k = 0.001 min −1 ) and g-C3 N4 ( k = 0.012 min −1 ), showing excellent photocatalytic activity against organic pollutants.